A new absolute date from Swartkrans Cave for the oldest occurrences of Paranthropus robustus and Oldowan stone tools in South Africa. Issue 156 (July 2021) - Kuman, Kathleen; Granger, Darryl E.; Gibbon, Ryan J.; Pickering, Travis Rayne; Caruana, Matthew V.; Bruxelles, Laurent; Clarke, Ronald J.; Heaton, Jason L.; Stratford, Dominic; Brain, C.K.
Abstract: The Early Pleistocene site of Swartkrans in South Africa's Cradle of Humankind World Heritage Site has been significant for our understanding of the evolution of both early Homo and Paranthropus, as well as the earliest archaeology of southern Africa. Previous attempts to improve a faunal age estimate of the earliest deposit, Member 1, had produced results obtained with uranium-lead dating (U–Pb) on flowstones and cosmogenic burial dating of quartz, which placed the entire member in the range of >1.7/1.8 Ma and <2.3 Ma. In 2014, two simple burial dates for the Lower Bank, the earliest unit within Member 1, narrowed its age to between ca. 1.8 Ma and 2.2 Ma. A new dating program using the isochron method for burial dating has established an absolute age of 2.22 ± 0.09 Ma for a large portion of the Lower Bank, which can now be identified as containing the earliest Oldowan stone tools and fossils of Paranthropus robustus in South Africa. This date agrees within one sigma with the U–Pb age of 2.25 ± 0.08 Ma previously published for the flowstone underlying the Lower Bank and confirms a relatively rapid rate of accumulation for a large portion of the talus.